Democracy and the rise of women's movements in Sub-Saharan Africa - Fallon, Kathleen M. (Johns Hopkins University Press, 2008)
"Despite a late and fitful start, democracy in Africa, Latin America, and Eastern Europe has recently shown promising growth. Kathleen Fallon discusses the role of women and women's advocacy groups in furthering the democratic transformation of formerly autocratic states."--Jacket